THE URGENCY OF SEXUAL EDUCATION FOR ADOLESCENTS IN INDONESIA AGAINST SECULARISM (CASE STUDY OF PERMENDIKBUD-RISTEK POLICY NUMBER 30 OF 2021) - Sintya Kartika Prameswari; Fajar Nur Syah Alam; Naufal Akmal Syammary (International Conference on Social and Islamic Studies, 2021)
The public is highly concerned about moral deterioration in situations of sexual abuse in Indonesian colleges. The Minister of Education, Culture, Research, and Technology released Regulation Number 30 of 2021 addressing the prevention and treatment of sexual violence in universities as a response to this problem. But however, the substance of sexual violence in this regulation includes the paradigm of sexual consent which recognizes that an agreement between two perpetrators is not a criminal conduct, resulting in opposition from a wide range of parties. As a result of this situation, it appears as if religious principles are irrelevant, and that advantage takes precedence over sharia. The researcher proposes a solution in this article through learning in the context of sexual education for adolescents. So that they do not think wrongly and act in various ways. This study uses a library research method that refers to contemporary books as primary sources, scientific journals, and websites as secondary references. Technical analysis employs of a traditionalist-philosophical approach that examines phenomena that are irrelevant and not in line with norms and religious values.